P200 family protein IFI204 negatively regulates type I interferon responses by targeting IRF7 in nucleus. - Liu Cao; Yanxi Ji; Lanyi Zeng; Qianyun Liu; Zhen Zhang; Shuting Guo; Xiaolong Guo; Yongjia Tong; Xiaolu Zhao; Chun-Mei Li; Yu Chen; Deyin Guo (PLoS Pathogens, 2019)
Interferon-inducible p200 family protein IFI204 was reported to be involved in DNA sensing, and subsequently induces the production of type I interferons and proinflammatory mediators. However, its function in the regulation of antiviral innate immune signaling pathway remains unclear. Here we reported a novel role of IFI204 that specifically inhibits the IRF7-mediated type I interferons response during viral infection. IFI204 and other p200 family proteins are highly expressed in mouse hepatitis coronavirus-infected bone marrow-derived dendritic cells. The abundant IFI204 could significantly interact with IRF7 in nucleus by its HIN domain and prevent the binding of IRF7 with its corresponding promoter. Moreover, other p200 family proteins that possess HIN domain could also inhibit the IRF7-mediated type I interferons. These results reveal that, besides the positive regulation function in type I interferon response at the early stage of DNA virus infection, the interferon-inducible p200 family proteins such as IFI204 could also negatively regulate the IRF7-mediated type I interferon response after RNA virus infection to avoid unnecessary host damage from hyper-inflammatory responses.